Strengthening Collaborative Governance: A Penta Helix Approach to Accelerate Stunting Reduction in Kampar Regency - Pratama, Andika Yuli; Andri, Seno; Yuliani, Febri; As’ari, Hasim (Journal of Posthumanism, 2025)
This study examines the implementation of collaborative governance strategies involving government, private sector, community, educational institutions, and non-governmental organizations to accelerate stunting reduction in Kampar Regency. Using the Penta Helix collaboration model and collaborative governance theory as the conceptual framework, the research identifies key factors supporting successful collaboration, challenges faced, and strategies to overcome them. This study employs a qualitative case study approach, collecting primary data through in-depth interviews with government officials, private sector representatives, community leaders, academic experts, and NGOs, as well as analyzing secondary sources such as policy documents and program reports. Data analysis follows thematic coding to ensure a rigorous examination of collaborative governance dynamics. Through this case study approach, this study highlights the importance of effective coordination, resource integration, community empowerment, and sustainable capacity-building. The recommendations provided aim to strengthen collaborative governance practices and enhance the effectiveness of stunting reduction programs, contributing to broader efforts in improving child welfare in Kampar Regency.